Creative Economy Development and Digitalization of MSMEs in Made Village, Surabaya - Panjaitan, Ade Rizky; Akbar, Ahmad Taufik; Maharani, Ida Ayu Putu Savitri Dewi; Shafira, Jihan; Pujiarto, Trimono (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service article titled "Creative Economy Development and Digitalization of MSMEs in Made Village, Surabaya" addresses the challenge of low digital literacy and limited access to technology faced by MSMEs in Made Village, an urban village marked by social economic disparities within an elite area. The methodology employed includes a structured workshop on "Content Creating for Branding" and the establishment of a digital assistance post for registering MSMEs on platforms such as GoFood and implementing QRIS-based digital payments. These interventions are supported by a participatory approach integrating MSME development theories, digital payment concepts, e-commerce utilization, and digital location marketing via Google Maps. The activities were implemented over one month with intensive mentorship to ensure practical application and sustainable digital transformation. Outcomes showed significant enhancement in digital adoption, branding awareness, and operational efficiency among local MSMEs, contributing to broader market access and increased competitiveness. The program effectively promoted inclusive economic growth and urban sustainability, directly supporting SDGs 8 and 11. This study highlights the vital role of collaborative, context-sensitive interventions in bridging digital divides and fostering creative economic development in marginalized urban communities. Artikel pengabdian masyarakat berjudul "Pengembangan Ekonomi Kreatif dan Digitalisasi UMKM di Kelurahan Made, Surabaya" ini mengkaji permasalahan rendahnya literasi digital dan keterbatasan akses teknologi yang dihadapi pelaku UMKM di Kelurahan Made, sebuah kelurahan urban yang memiliki kesenjangan sosial ekonomi di tengah kawasan elit. Metode yang digunakan meliputi pelatihan terstruktur berupa workshop "Content Creating for Branding" serta pendirian posko digital yang membantu pendaftaran UMKM pada platform seperti GoFood dan implementasi pembayaran digital berbasis QRIS. Intervensi ini didukung dengan pendekatan partisipatif yang mengintegrasikan teori pengembangan UMKM, konsep pembayaran digital, pemanfaatan e-commerce, serta pemasaran lokasi digital melalui Google Maps. Kegiatan ini dilaksanakan selama satu bulan dengan pendampingan intensif agar penerapan digitalisasi dapat dilakukan secara praktis dan berkelanjutan. Hasilnya menunjukkan peningkatan signifikan dalam adopsi teknologi digital, pemahaman branding, dan efisiensi operasional UMKM lokal, yang secara langsung memperluas akses pasar serta meningkatkan daya saing usaha. Program ini berhasil mendorong pertumbuhan ekonomi inklusif dan keberlanjutan perkotaan, serta selaras dengan target SDGs 8 dan 11. Studi ini menegaskan pentingnya intervensi kolaboratif yang sensitif terhadap konteks lokal dalam menjembatani kesenjangan digital dan mendorong pengembangan ekonomi kreatif di komunitas urban yang terpinggirkan.